Teachers’ Perspectives of Strategies on Managing Students’ Misbehavior during Synchronous Online Learning - Refi Aksep Sativa; Didi Sukyadi; Pupung Purnawarman (Universitas Muhammadiyah Semarang, 2022)
The worldwide pandemic has compelled the teaching and learning process to be conducted entirely online. Having expertise in teaching in a face-to-face setting does not ensure success in dealing with students’ misbehavior in synchronous online classrooms. The behavior issues that arose during virtual learning have increased both teachers’ and students’ stress levels and disrupted the flow of the lessons. The purpose of this paper was to collect examples of students’ misbehavior and the strategies employed by the teachers to address them in an online class. A phenomenology case study was used to study the participants’ experience. An online survey was used to ask open-ended and closed-ended questions, with an interview following to discuss the results in more significant detail. This study enlisted the help of twenty-two English teachers who taught synchronous online classes. The findings offered some practical solutions for dealing with behavior issues in online learning and suggestions for further research.